Investigation of the effect of the Reservoir Rock Compressibility on Oil Recovery Factor during Gas Injection - Naser, Madi; Khalifa, Abdulhadi; Nasr, Alla; Akhlasa, Enas (Journal of Pure & Applied Sciences, 2023)
A type of EOR, secondary production includes water flooding and gas injection. Normally, gas is injected into the gas cap and water is injected into the production zone to sweep oil from the reservoir. A pressure-maintenance program can begin during the primary recovery stage, but it is a form of enhanced recovery. The main purpose of this report is to investigate the effect of the reservoir rock compressibility on oil recovery factor during gas injection. The problem statement of this study is firstly, as the reservoir oil and gas production under primary conditions, causes the reservoir pressure to decline. Secondly, A gas injection is required to re-energize or “re-pressurize" the reservoir. The main objective of this project is to investigate the effect of the reservoir fluid densities on oil recovery factor during gas injection. By using ECLIPES Software, we model the data and find out the best prediction of gas injection that is suitable for the available field data. It is proven that the optimum oil production is by injection a high amount of injection rate. The highest increase in percentage of the total gas production is when an injection of 54 MMSCF is 0.58 %.  The higher the compressibility value of the rock, will give the higher the rate of oil and gas production. The relationship between oil rate, gas rate, pressure, and oil recovery factor are directing the compressibility of rocks is a direct relationship.